The many facets of miR‐223 in cancer: Oncosuppressor, oncogenic driver, therapeutic target, and biomarker of response. (5th May 2021) - Favero, Andrea; Segatto, Ilenia; Perin, Tiziana; Belletti, Barbara
Abstract: Given their intrinsic pleiotropism, microRNAs (miR) play complex biological roles, in both normal and pathological conditions. Often the same miR can act as oncogene or oncosuppressor, depending on the biological process dysregulated in each specific tissue. miR‐223 does not represent an exception to this rule and its functions greatly differ in different contexts. miR‐223 has been widely studied in the hematopoietic compartment, where it plays a central role in innate immune response, regulating myeloid differentiation and granulocytes function. Accordingly, dysregulated expression of miR‐223 has been associated to different inflammatory disorders and tumors arising from the immune compartment. Most carcinomas, breast cancer being the most studied, display loss of miR‐223. However, in gastro‐esophageal cancers miR‐223 is frequently overexpressed and correlates with worse prognosis. A link between miR‐223 and response to CDK4/6‐inhibitors has been recently proposed, suggesting a role as biomarker of therapeutic response. The notion that one of the most commonly mutated protein in cancer, mutant p53, binds the promoter of miR‐223 and suppresses its transcription, adds a further level of complexity to the full understanding of miR‐223 in cancer. In this review, we will summarize the current knowledge on the molecular networks that alter or are altered by miR‐223, in different cancer types. We will discuss if the times are ready for the exploitation of miR‐223 as predictive biomarker of treatment response or, even, as therapeutic target, in specific settings. Finally, we will suggest which could be the next steps to be taken for a realistic clinical application of miR‐223. This article is categorized under: RNA in Disease and Development > RNA in Disease Abstract : miR‐223–centered view of the Hallmarks of Cancer. Many of the hallmarks of cancer can be affected by miR‐223 up‐regulation or down‐regulation, via different modulation of its targets and depending on the tumor type. These aspects of miR‐223 biology support the possibility that it could serve as prognostic/predictive biomarker and therapeutic target, in certain tumoral contexts.